Antenatal Sonographic Diagnosis of Pharyngeal Teratoma: Our Experience of a Rare Case with Review of the Literature - M. Varras; Ch. Akrivis; Ch. Plis; G. Tsoukalos (Hindawi Limited, 2009)
Background. Teratomas are the most common tumors. They are usually localized in the sacrococcygeal area, while the pharyngeal localization is very rare. The number of cases of stomatopharyngeal teratomas detected prenatally via sonography is very small. Case Report. We present the case of a 24-year-old primipara at 18 weeks' gestation, that at the routine ultrasound scan, the fetus was found with an echogenic mass, filling the stomatopharyngeal cavity and protruding from the mouth. Other abnormalities were not found. Termination of pregnancy was achieved using misoprostol. A female stillborn fetus with a weight of 250 g and length of 25.5 cm was delivered. The postmortem and pathologic examination confirmed the diagnosis. Conclusion. Pharyngeal teratomas can be diagnosed with the use of ultrasounds in utero facilitating parents' counseling in early time.